Single-incision laparoscopic surgery versus conventional laparoscopic appendectomy - K., Jawahar; R., Sharanya; Prakash, Sanjay (International Surgery Journal, 2018)
Background: Single Incision Laparoscopic Surgery (SILS) is a new technique of minimally invasive surgery using a single incision to minimize all ports to one site, hence a single scar that can be strategically placed in the umbilicus for a perceived scar less abdomen. Methods: We report this study evaluating the possible advantages of SILS versus conventional laparoscopic appendectomy through a randomized controlled trial. The study population includes patients diagnosed as acute appendicitis. A total of 50 patients underwent appendectomy, patients were randomly assigned to either SILS appendectomy or conventional appendectomy in 1:1 ratio. Primary end points were operative time, complication rate, postoperative pain, post-operative hospital stay and patient satisfaction. Results: The pain scores measured at 48 hours were significantly lower in SILS group than conventional Lap appendectomy group. Patients had significant satisfaction score and lower pain score in SILS group than Lap appendectomy group measured at 6 weeks after appendectomy. However, the post-operative stay was similar in both the groups. There was no conversion to open appendectomy in both the groups. Patient satisfaction score in SILA was found to be higher than CLA. Operating times were similar and post-operative stay was apparently lower. Conclusions: SIL appendectomy is as safe and effective as conventional lap appendectomy.